IMPLEMENTASI SOFTWARE METRICS UNTUK PENGUKURAN PERFORMA PADA SISTEM INFORMASI AKADEMIK UNIVERSITAS LAMPUNG (SIAKAD V.4.1 UNILA) - Anie Rose Irawati; Didik Kurniawan; Anastasya Cindy Grissherin (Jurnal Pepadun, 2022)
The University of Lampung Academic Information System (SIAKAD) is an information system developed to support the university in managing student academic processes. The absence of a feedback section makes users, especially students, unable to deliver opinions about the system, so that even though the system is running well, the real quality of the system based on user experience is unknown. Performance is one aspect of quality that is important to know, but it cannot be measured directly. The study uses an information system functional scoreboard to assess three aspects of the system, those are system performance, information effectiveness, and service performance. The questionnaire was distributed to 100 respondents from all faculties as a sample, which are expected to represent the answers from the entire university. Based on the research results, it is known that the performance of SIAKAD V.4.1 UNILA is good to a moderate extent. Some things that are needed to be improved are the stages of service procedures, the addition of other academic information such as graphs of student’s grade, transparency of grades, an updated course schedule, integration to the graduation registration system, adding the latest campus information that is displayed clearly and well, also integration with the other systems at the University of Lampung as well as better server replacement and maintenance.